Manihot cultivation yield using organic and chemical fertilizers in an acid soil (2017)
Cassava (Manihot esculenta) is the founh most important world food product after rice, wheat and corn, and is part of diet of more than 100 million people worldwide; therefore, it is necessary to implement its establishment in environmentally friendly agriculture conditions. This study aimed at determining the cassava crop yield, applying bokashi organic fertilizer at different doses. The experiment was conducted in the municipality of Ciénaga de Oro (Cordoba), where the variety ICA-costena with a 12 300 plants/ha density was established. At planting, 50 % of bokashi and vermicompost was incorporated, 25 % was added a month later, and the rest two months later. The treatments were 500, 1000, 1500 and 2000 kg ha-1 of bokashi, plus 200 kg.ha" of vermicompost, additionally a treatment without application, and a chemical treatment.The data were collected 240 days after the crop was established, and the evaluated variables were a) number of roots, b) dry root weight, c) harvest index, and d) total production per hectare. A randomized complete block design with four replications was used. The 74.57 % harvest index was the best response, and was obtained with 1500 kg ha-1 of boskashi and plus 200 kg.ha" of vermicompost. The highest number of roots, dry root mass, and yield were found with the application of 2000 kg ha‘l of bokashi plus 200 kg.ha-1 of vermicompost.